ENERGY EFFICIENCY ANALYSIS OF AGAPE BUILDING IN DUTA WACANA CHRISTIAN UNIVERSITY - Dewangga, Yordan (Unika Santo Thomas, 2023)
Duta Wacana Christian University (UKDW) as one of the tertiary institutions in the city of Yogyakarta is one of the sectors that utilize electrical energy to support daily activities. One of the buildings at UKDW that is used as an office center is the Agape building. Electrical energy is used as an energy source to support office and lecture activities such as artificial lighting (lamps) and artificial ventilation (AC). Based on this dependence, a study is needed to determine the extent to which the level of energy efficiency exists in the Agape building, especially the effect of artificial lighting and ventilation on electrical energy efficiency. The method used in this study is a quantitative method based on primary data and secondary data. Primary data was obtained through direct measurements regarding the amount of energy used in one working day (8 hours), while secondary data was used to determine the dimensions and spaces in the Agape building. Based on the results of the energy efficiency analysis of artificial lighting and ventilation that has been carried out, it is known that the level of electrical energy used for artificial lighting and ventilation in the Agape building is classified as efficient. The results of this study are expected to be used as material for evaluation and consideration for subsequent research in order to achieve energy efficiency.